2023
DOI: 10.1002/ange.202215522
|View full text |Cite
|
Sign up to set email alerts
|

A Deep‐Blue‐Emitting Heteroatom‐Doped MR‐TADF Nonacene for High‐Performance Organic Light‐Emitting Diodes**

Abstract: We present a p-and n-doped nonacene compound, NOBNacene, that represents a rare example of a linearly extended ladder-type multiresonant thermally activated delayed fluorescence (MR-TADF) emitter. This compound shows efficient narrow deep blue emission, with a λ PL of 410 nm, full width at half maximum, FWHM, of 38 nm, photoluminescence quantum yield, Φ PL of 71 %, and a delayed lifetime, τ d of 1.18 ms in 1.5 wt % TSPO1 thin film. The organic lightemitting diode (OLED) using this compound as the emitter shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…At about the same time as Hatakeyama et al , Zysman-Calman et al independently reported the synthesis of ladder-type deep-blue MR compounds NBONacene and MesBDIDOBNA-N using a protocol which can be categorized as sequential multiple borylations (Scheme 38). 253,254 One-pot borylation afforded p MDBA-Br in 73% yield, with subsequent coupling giving the final borylation precursors in 47% and 57% yields, respectively. One-shot borylation was performed with excess BBr 3 , and the R2BBr species generated in situ were trapped with a Grignard reagent to afford the target compounds, NBONacene and MesB-DIDOBNA-N , in 45% and 74% yields, respectively.…”
Section: One-shot Borylationmentioning
confidence: 99%
“…At about the same time as Hatakeyama et al , Zysman-Calman et al independently reported the synthesis of ladder-type deep-blue MR compounds NBONacene and MesBDIDOBNA-N using a protocol which can be categorized as sequential multiple borylations (Scheme 38). 253,254 One-pot borylation afforded p MDBA-Br in 73% yield, with subsequent coupling giving the final borylation precursors in 47% and 57% yields, respectively. One-shot borylation was performed with excess BBr 3 , and the R2BBr species generated in situ were trapped with a Grignard reagent to afford the target compounds, NBONacene and MesB-DIDOBNA-N , in 45% and 74% yields, respectively.…”
Section: One-shot Borylationmentioning
confidence: 99%
“…Firstly, the investigation of π-extended MR-TADF molecules containing more than three boron atoms has been relatively limited due to constraints in molecular design and synthesis 19 . Secondly, as delineated in Scheme S1, current examples primarily concentrate on linearly extended skeletons 15,[20][21][22] , with a scarcity of research on molecules featuring diverse topologies, where V-DABNA, ω-DABNA and some derivatives stand as rare exceptions [23][24][25] . Consequently, elucidating the structure-property relationship among higher-order B,N-motifs remains challenging, thereby hindering the development of advanced emitters.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, a signi cant hurdle for the development of MR-TADF materials lies in their slow spin-ip process. [7][8][9][10][11] Most MR-TADF structures exhibit comparable locally excited (LE) features in their singlet and triplet excited states. 12 According to El-Sayed's rule, 13 the spin-orbit coupling (SOC) matrix element between singlet and triplet states with the same type of orbital is vanishingly tiny, making this spin ipping ( 1 LE→ 3 LE) in MR-TADF structures forbidden.…”
Section: Introductionmentioning
confidence: 99%